2022
DOI: 10.3389/fnagi.2022.991157
|View full text |Cite
|
Sign up to set email alerts
|

Regular fecal microbiota transplantation to Senescence Accelerated Mouse-Prone 8 (SAMP8) mice delayed the aging of locomotor and exploration ability by rejuvenating the gut microbiota

Abstract: Recent evidence points out the role of the gut microbiota in the aging process. However, the specific changes and relevant interventions remain unclear. In this study, Senescence Accelerated Mouse-Prone 8 (SAMP8) mice were divided into four groups; young-FMT-group transplanted fecal microbiota from young donors (2–3°months old) and old-FMT-group transplanted from old donors (10–11°months old); additionally, other two groups either adult mice injected with saline solution or untreated mice served as the saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…SAMP8 is a common model for studying accelerated aging ( Morley et al, 2012 ; Cheng et al, 2014 ). In line with previous studies, we found that the SAMP8 mice had significantly fewer neurons, as shown by Nissl staining ( Figures 1A , B ) ( Yang X. et al, 2020 ; Yang H. H. et al, 2020 ; Zhang N. et al, 2022 ; Zhang Y. et al, 2022 ). This result, together with the two-photon analysis, indicated that the SAMP8 mice show significant neuroinflammation and BBB disruption ( Figure 1C ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…SAMP8 is a common model for studying accelerated aging ( Morley et al, 2012 ; Cheng et al, 2014 ). In line with previous studies, we found that the SAMP8 mice had significantly fewer neurons, as shown by Nissl staining ( Figures 1A , B ) ( Yang X. et al, 2020 ; Yang H. H. et al, 2020 ; Zhang N. et al, 2022 ; Zhang Y. et al, 2022 ). This result, together with the two-photon analysis, indicated that the SAMP8 mice show significant neuroinflammation and BBB disruption ( Figure 1C ).…”
Section: Discussionsupporting
confidence: 93%
“…SAMP8 mice are a common model of accelerated aging that have cognitive and intestinal problems as they age ( Yamamoto et al, 2015 ; Ben Othman et al, 2020 ; Chen et al, 2021 ). The gut-brain axis, which is the bidirectional communication between the gut and the brain ( Xie et al, 2020 ; Chen et al, 2021 ; Zhang N. et al, 2022 ; Zhang Y. et al, 2022 ), may be involved in these problems ( Xie et al, 2020 ; Yang X. et al, 2020 ; Yang H. H. et al, 2020 ; Yang D. et al, 2023 ; Yang X. Q. et al, 2023 ). Many studies have shown that gut dysbiosis, which is the imbalance of the gut microbiota, is associated with not only gastrointestinal diseases, but also the physiology and inflammation of the central nervous system ( Ma et al, 2019 ; Rutsch et al, 2020 ; Morais et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the rate of Akkermansia in older mice is typically not more than ~10% on healthy diets [ 78 ]. However, at least one study showed that under fecal transplantation conditions, Akkermansia can dramatically rise with age [ 79 ] and reduce senescence. Perhaps most relevant to our findings is a study showing Akkermansia levels in mice fed beef protein diets averaging 12.68%, but with ranges of up to 52% in some individuals, suggesting a potentially significant effect of protein type [ 80 ].…”
Section: Discussionmentioning
confidence: 99%